In-vitro α-Glucosidase inhibitory potential of extracts from musa paradisiaca - Khamsah Suryati, Mohd; U.S. Mahadeva, Rao; Abdurrazak, Muhammad (2015)
Recently, there has been increased interest in the development of alternative medicines for type II Diabetes mellitus, notably the screening of phytochemicals with ability to delay or even prevent completely the absorption of glucose. The aim of this study was to investigate the invitro inhibitory effect of Musa Paradisiaca flesh, skin and tepal extracts on the key enzyme linked to diabetes i.e α-glucosidase (EC 3.2.1.20). The inhibitory effect of these extracts on α-glucosidase activities was performed. The results revealed that methanolic extract of M. Paradisiaca tepal was the most potent inhibitor of α-glucosidase (with IC50 60±0.14 µg/ml), followed by the ethanolic tepal extract( with IC50 200±0.19) and then the aqeous tepal (with IC50 360±0.62) respectively . No inhibition was observed in the skin, flesh methanolic extracts and ofcourse acarbose under our assay condition. It can be inferred from this study that the α-glucosidase inhibitory potential of M. Paradisiaca may be due to the presence of phytochemicals such as glycosides and flavonoids. However, further study is required to isolate the enzyme inhibitory component of this plant.